Friction stir processing of hybridized AZ31B magnesium alloy-based composites by adding CeO2 and ZrO2powders: mechanical, wear, and corrosion behaviors - Shoufa Liu; Moslem Paidar; Olatunji Oladimeji Ojo; Michaela Šlapáková Poková; Sadok Mehrez; Azlan Mohd Zain; Qiaorong Zhao; Jinpeng Wang (Journal of Materials Research and Technology, 2023)
To improve the properties of AZ31B Mg alloy and for the first time, the rare earth cerium oxide (CeO2) and zirconium dioxide (ZrO2) were combined for synergistic benefits and introduced into the structural AZ31B magnesium alloy through the solid-state friction stir processing procedure to form the hybridized AZ31B Mg/ZrO2+CeO2 composites under variable levels of the tool's rotational speed up to 1200 rpm. The macro-/microstructure, hardness, shear punching strength, tensile strength, corrosion behaviours, and tribological characteristics such as weight/wear loss, wear rate, coefficient of friction, worn surfaces, and debris of the AZ31B Mg/ZrO2+CeO2 hybrid composites were investigated and compared. The results indicated that void, tunnel defect, and ZrO2+CeO2 agglomeration could not be prevented at low speed (800 rpm) while defect-free composites were obtained at high speed (1200 rpm). Grain refinement from 7.39 μm to 3.38 μm and the ZrO2+CeO2 fragmentation (4.52–2.49 μm) ensued after a rise in the tool's rotational speed owing to higher plastic straining, dynamic recrystallization, and ZrO2+CeO2 particle-aided pinning effects. Improvements in hardness (99–135 HV), shear punching strength (121–237 MPa), tensile strength (172–228 MPa) and wear properties of the composite were attained due to the defect elimination, inherent finer Mg grains, and the uniformly dispersed ZrO2+CeO2 particles. These attributes also enhanced the corrosion resistance of the AZ31B Mg/ZrO2+CeO2 composite at the elevated rotating speed of the tool. The combination of the CeO2 and ZrO2 particles is an effective particle-blend for improving the properties of Mg alloy to expand its application scope.